Predictors of self-care behaviors and glycemic control among patients with type 2 diabetes mellitus - Babazadeh, Towhid; Lotfi, Yosef; Ranjbaran, Soheila (Frontiers in Public Health, 2023)
Aims This study used the Extended Theory of Reasoned Action (ETRA) to predict self-care behaviors and HbA1c among patients with type 2 diabetes in Iran. Materials and methods A cross-sectional study was performed using a multistage random sample. A total of 240 patients with type 2 diabetes, who were referred to the diabetes healthcare centers in Chaldoran, participated in the research. Instruments consisting of standardized questionnaires were used based on the Extended Theory of Reasoned Action (ETRA) constructs and the summary scale of diabetes self-care behaviors measure. Findings The results of this study demonstrated that demographic variables explained 7% (p-value = 0.23) and ETRA constructs 18% of the variance (p-value = 0.02) in behavioral intention, respectively. According to the hierarchical multiple linear regressions on self-care behaviors, demographic factors (p-value 0.001) dictated 45.7% of the variation of the self-care behavior, while knowledge, attitude, self-efficacy, and behavioral intention (p-value 0.001) accounted for 63.4% of the variance. The ETRA constructs, self-care practices, and demographic factors together account for almost 57% of the variation in the HbA1c. Self-care practices were the best indicator of HbA1c (β = −0.593). Conclusion ETRA constructs and self-care behavior can be the best determinants of HbA1c level in type 2 diabetes. This model is suggested to be applied in designing intervention programs to improve HbA1c in these groups of patients.